Mobile Metropolises : Urban Transport Matters - Independent Evaluation Group (World Bank, Washington, DC, 2017)
The evaluation exercise focuses on three themes that cut across strategies and project designs during FY07–16: mobility for all (including the poor, women, and persons with disabilities), sustainable service delivery, and institutional development. In spite of the pressing need arising from rapid urbanization, Africa has a declining urban transport portfolio that in the second half of the review period (FY12–06) focused increasingly on urban roads. Upper-middle-income countries represent 43 percent of the evaluation portfolio commitments.Overall, the World Bank Group has been effective in supporting improved service quality and increased access, but approaches based on increasing infrastructure capacity are not balanced with approaches based on demand management. Among disadvantaged groups the poor received the most support. Much less attention was paid to the special needs of women and disabled persons.Affordability of urban transport services is rarely analyzed in the World Bank Group’s projects, with unknown impact on the mobility of the disadvantaged. Financial sustainability remains a challenge for the provision of public transport services. Financing gaps between revenues and operation and maintenance costs are common. The World Bank is often optimistic in appraising the costs, timing, and financial viability of mass transit projects.Efforts to engage the private sector to achieve operational efficiencies and improved financing seldom combine the policy and institutional strengths of the World Bank with transactional strengths of the International Finance Corporation and the Multilateral Investment Guarantee Agency.The World Bank Group has achieved localized environmental mitigation benefits along key urban transit corridors or systems, but broader environmental benefits could be still be achieved by using a comprehensive approach that combines upstream (policy and sector framework) and downstream (operational) measures.Weak institutional capacity and coordination remains a critical challenge in the urban transport sector. Institutional development support is a part of 80 percent of World Bank Group projects, yet these often focus on a single local body during a one-time project. Longer-term and more ambitious institutional reform engagements occurred in only a few cities.The World Bank Group’s contribution to urban transport development goes beyond projects. Investments often provide a platform for the World Bank Group to offer guidance, training, technical assistance, and learning throughout the project cycle, South-South learning and exchange, and good practices for demonstration to sector stakeholders and further adoption.